EVALUATION OF THE SUITABILITY OF MANGROVE RIVER COASTAL WATER FOR SEA CUCUMBER CULTIVATION - Chotimah, Husnul; Manis Suharjo; Suhartini (PT. Jurnal Center Indonesia Publisher, 2025)
This study aimed to evaluate the suitability of the coastal waters of Sungai Bakau, Kumai District, as an alternative site for sea cucumber (Holothuria scabra) aquaculture. Water quality parameters, including temperature, salinity, and pH, were monitored, along with the growth performance of sea cucumbers in terms of body weight and length during the cultivation period. The results showed water temperatures ranging from 28–31°C, pH values between 8.3–8.7, and an average salinity of 20.5 ppt. Although the salinity was slightly below the optimal range (28–32 ppt), the sea cucumbers demonstrated positive growth. Final measurements indicated an increase in body weight from 10–20 grams to an average of 0.29 kg, and in body length up to 16.7 cm over approximately three months of cultivation. These findings suggest that the coastal waters of Sungai Bakau have potential for sea cucumber aquaculture development, with some adjustments needed to optimize salinity conditions.